Development of Educational Games to Improve Students’ Understanding of Basic Arithmetic Operations Based on Monte Carlo Algorithms - Iru, Anjelita Ndauki; Arini Aha Pekuwali; Reynaldy Thimotius Abineno (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study aims to develop an educational game to improve the understanding of basic arithmetic operations for fourth-grade students of SDM Pahomba. Application development uses the Multimedia Development Lie Cycle (MDLC) method which consists of 6 phases: Concept, design, material collecting, assembly, testing, and distribution. In addition, the Monte Carlo Algorithm is applied to generate random questions to create a more interesting and adaptive learning process. The results of this study prove that the use of educational games is effective in improving students’ understanding of basic arithmetic operations. This is evidenced by the success of black box testing which ensures all features function properly. And evidenced by a significant increase in the average score of 19 students, namely from a pre-test score of 45.25 to 84 during the post-test. This success is strengthened by the results of the calculation of the percentage of effectiveness of 85%. So the conclusion is that this educational game application is worthy of being used as a learning tool to improve students’ understanding of basic arithmetic operations.